Characterization of Extracellular Vesicles from Human Saliva: Effects of Age and Isolation Techniques - Lucia Reseco; Angela Molina-Crespo; Mercedes Atienza; Esperanza Gonzalez; Juan Manuel Falcon-Perez; Jose L. Cantero (Cells, 2024)
Salivary extracellular vesicles (EVs) represent an attractive source of biomarkers due to the accessibility of saliva and its non-invasive sampling methods. However, the lack of comparative studies assessing the efficacy of different EV isolation techniques hampers the use of salivary EVs in clinical settings. Moreover, the effects of age on salivary EVs are largely unknown, hindering the identification of salivary EV-associated biomarkers across the lifespan. To address these questions, we compared salivary EV concentration, size mode, protein concentration, and purity using eight EV isolation techniques before and after magnetic bead immunocapture with antibodies against CD9, CD63, and CD81. The effects of age on salivary EVs obtained with each isolation technique were further investigated. Results showed higher expression of CD63 on isolated salivary EVs compared to the expression of CD81 and flotillin-1. Overall, magnetic bead immunocapture was more efficient in recovering salivary EVs with Norgen’s Saliva Exosome Purification Kit and ExoQuick-TC ULTRA at the cost of EV yield. Regardless of age, Invitrogen Total Exosome Isolation Solution showed the highest level of protein concentration, whereas Izon qEVOriginal-70nm columns revealed the highest purity. This study provides the first comprehensive comparison of salivary EVs in younger and older adults using different EV isolation techniques, which represents a step forward for assessing salivary EVs as a source of potential biomarkers of tissue-specific diseases throughout the life cycle.